New models for old: Funding UWI for the long haul - West Indies Group of University Teachers (Jamaica) - Devonish, Hubert (My University, 2015)
This presentation is based on a notion that higher education and The University of the West Indies (UWI), in particular, constitute economic activities that must be incentivized in the same way that other productive enterprises are. It argues that UWI provides both significant immediate contributions to the economies and GDP of campus territories, in addition to providing the public good for which they were set up. The contributing territories are becoming increasingly reluctant or unable, depending on one's perspective, to fund the students for which they have responsibility at UWI, according to the existing funding arrangement. The consequence is that UWI is in an ongoing battle for survival, with shrinking financing from the governments, and expectations of doing more with less. The presentation seeks to shake that perception that UWI is a drag on the public purse by proving, in relation to the operations of UWI in Jamaica 2011, that the Government of Jamaica, through taxation and statutory deductions, as well as consumption taxes, collected from the operations of UWI approximately the same sum as its subvention to UWI in that same year. This was in addition to the benefits in relation to foreign exchange earnings of the country. Using UWI as a model, the presentation posits that the net contribution to UWI from its campus territory contributors is at or very close to zero. In effect, the public good for which UWI has been set up, is being provided for free. The presentation poses the problem of how that public good can be paid for since, if it is not, the goose that lays the golden egg will die for the want of feed. It goes on to explore a variety of models for funding UWI, which would both enhance its immediate economic benefits to the contributing territories, while also funding UWI in its public good mission. These models are based on the notion of UWI functioning as a provider of higher education services within the global marketplace.
Contribution to the Panel on Strategies for Financing Higher Education: The Impact of Political, Economic and Social Contexts at the Regional Conference on Institutionalising Best Practice in Higher Education, UWI, St. Augustine, Trinidad and Tobago, 24-26 June, 2015.
Keywords: Higher education; Educational finance; Financial support; The University of the West Indies; The University of the West Indies, Mona; Jamaica; Caribbean